2019
DOI: 10.1039/c9nr05684j
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment responsive FePt/MoS2 nanocomposites with chemotherapy and photothermal therapy for enhancing cancer immunotherapy

Abstract: As a multifunctional platform for photo-chemo-immunotherapy strategies, FePt/MoS2 nanocomposites shows great potential in cancer theranostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…The EE and DL of the FBPD NPs were calculated by UV spectrophotometry. UV-spectra of Dox dispersed in saline at different concentrations (20,25,30,35,40, and 50 µg/mL) and the corresponding relationship between concentrations of Dox and absorbance ( Fig. 2e, 2f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EE and DL of the FBPD NPs were calculated by UV spectrophotometry. UV-spectra of Dox dispersed in saline at different concentrations (20,25,30,35,40, and 50 µg/mL) and the corresponding relationship between concentrations of Dox and absorbance ( Fig. 2e, 2f).…”
Section: Resultsmentioning
confidence: 99%
“…One probable approach to optimize their therapeutic effects is to combine PTT with other types of treatments. It was reported that PTT and chemo-drug synergistically enhance the antitumor effect to a great extent [21][22][23][24][25]. Due to the post-X-ray bombardment, the secondary electrons were distributed to enhance the EPR effect, and consequently, high-Z nanomaterials could optimize the passive tumor targeting.…”
Section: Introductionmentioning
confidence: 99%
“…anchored the following three components, i) FePt nanoparticles, which also has Fenton catalyst‐like property, ii) folic acid, and iii) CpG oligonucleotide onto the surface of molybdenum sulfate (MoS 2 ) nanosheets, to construct nanocomposites for combination therapy. [ 64 ] As anticipated, the ferroptosis agent, FePt, produced cytotoxic ROS through Fenton reaction, and the MoS 2 presented effective photothermal effect under NIR laser irradiation. Further, the CpG oligonucleotide induced antitumor immunity with the help of anti‐cytotoxic T‐lymphocyte‐associated protein 4 checkpoint‐blockade.…”
Section: Reactive Oxygen Species In Tumor Microenvironmentmentioning
confidence: 85%
“…Interestingly, FePt nanoparticles, a novel ferroptosis agent, could induce ferroptosis by catalyzing the Fenton reaction to produce the ROS. Meanwhile, the metastatic tumors are abolished effectively with the support of oligodeoxynucleotides containing cytosine-guanine together with systemic checkpoint blockade immunotherapy using an anti-CTLA4 (anti-cytotoxic T lymphocyte associated antigen-4) antibody [145], providing a multifunctional platform for anticancer therapeutic applications through ferroptosis. Targeting ferroptosis holds novel promise for the treatment of cancer and considerable efforts are being made to generate ferroptosis modulators for clinical use, but additional studies are required to devise the most efficient strategies in epigenetic and metabolic regulation of ferroptosis.…”
Section: The Cancer Therapeutic Application In Epigenetic and Metabolmentioning
confidence: 99%